System Change, Not Climate Change: Charting Alternative Responses to the Climate Crisis through International Comparative Research - Bodrožić, Zlatko; Adler, Paul (Journal of Management Studies, 2025)
The climate crisis challenges management scholars to address the system‐level factors that constrain and enable firms’ climate action. We argue that to meet this challenge, we need to study the climate action capacity of alternative systems of political‐economic power. We proceed in three steps. First, we develop a historically grounded map of four main types of power systems: ‘Oligarchy’, ‘Localism’, ‘Authoritarianism’, and ‘Democratization’. These types represent analytical categories – not clichéd labels – to examine alternative responses to the climate crisis. Second, we use this map to compare four cases in the taxi transportation sector, a sector which exemplifies the confluence of the digital and green revolutions in today’s political‐economic landscape. Our analysis of these cases suggests that Oligarchy’s climate action capacity is weak because its climate action is limited to what is profitable for the dominant firms. Oligarchy has been challenged by Authoritarianism, whereas Localism and Democratization have yet to yield stable alternatives. Building on these insights, in the third step we identify three priorities for strengthening our field’s capacity for relevant climate action research: (a) a focus on the systems within which firms are embedded, (b) a focus on political‐economic power, and (c) a programme of international comparative research.